The relationship between dental complexity and mandibular shape: implications for dietary inference in stem mammals - Harris, Wade (University of the Witwatersrand, Johannesburg, 2024)
Non-mammalian cynodonts exhibit some of the first major morphological innovations that contributed to the success of their descendent lineage, mammals. This includes features that are hypothesized to enable adaptation to a highly varied suite of diets such as specialized tooth crowns with complex occlusal surfaces and a jaw muscle configuration where two major muscles contribute to jaw closing. Surprisingly, inferences on cynodont diets so far have been based on qualitative evidence, and the quantification of these dietary adaptations could assist in testing these inferences. Here, I evaluate the relationships of mandibular shape, dental complexity and the combined data on body mass and relative mandible size, to known diets in living mammals, to assess the utility of these ecomorphological proxies for inferring the diets of extinct non-mammalian cynodonts. To assess relationships between diet and jaw shape, I collected 12 fixed landmarks (type 2) and four sliding landmarks (type 3) for six non- mammalian cynodonts, 51 marsupial mammals and 211 placental mammals. Dental complexity (OPCR) values were collected using the R package molaR, for a sample of 19 non-mammalian cynodonts, 47 marsupial mammals and 193 placental mammals. Procrustes-aligned shape coordinates, OPCR values, body mass estimates and relative mandible size data were then subjected to phylogenetic Procrustes ANOVA regressions and phylogenetic regressions. Neither mandible shape nor OPCR are strongly correlated to diet (carnivory, frugivory, granivory, herbivory, nectivory, invertivory), but the combination of these variables are a somewhat reliable predictor of diet, particularly mandible shape. Extinct non-mammalian cynodonts have mandible shapes that are comparable to those of mammals, however they occupy a narrow morphospace and their OPCR scores are generally much lower than those of mammals. Consequently, when these variables were entered into a predictive framework for diet, I observed limited inferential power since non-mammalian cynodonts do not strongly resemble mammals.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Palaeontology, Johannesburg 2024
Keywords: Non-mammalian cynodonts; Macroevolution; Dental complexity; UCTD; SDG-17: Partnerships for the goals